PHYSIOCHEMICAL ANALYSIS OF PRETREATED BIOMEDICAL WASTES - S, Sreeremya; P, Rajiv (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The main objective of the research is to pretreat the Category III biomedical waste using Bacillus flexus and to assess the physiochemical properties of pretreated biomedical waste. Methods: Major pretreatment methods such as physical (P), chemical (C), biological (using B. flexus) (B), physical and chemical, and physical, chemical, and biological method (PCB) were adopted for this investigation. The nutritional status was analyzed before and after the pretreatment. The physiochemical parameters such as pH, electrical conductivity, moisture content, bulk density, cellulose content, and carbohydrate content were assessed. Results: There was a significant difference between before and after the pretreatments of physiochemical properties. By treating, the biomedical waste with B. flexus has produced a drastic change in the cellulose level. By the assessment of each parameter before and after the pretreatment, the percentage of cellulose levels was found to be 35-40 in PCB method. Conclusions: Hence, the study concludes that the pretreated biomedical waste contains suitable physiochemical properties, which may be used as a substrate for the production of vermicompost.